Effect of Abiotic Factors on the Incidence of African Rice Gall Midge, Orseolia oryzivora and its Parasitism by Platygaster diplosisae and Aprostocetus procerae - Ogah, E.O.; Owoh, E.E.; Nwilene, F.E.; Ogbodo, E.N. (2012)
African rice gall midge (AfRGM), Orseolia oryzivora is one of the most damaging insect pests of lowland rice in Nigeria in the recent time, and could result in total crop failure in endemic areas. Of all the control measures adopted so far biological control is the most promising. Two parasitoids (Platygaster diplosisae, Hym: Platygastridae and Aprostocetus procerae, Hym: Eulophidae) have been identified with the potential to suppressed AfRGM population. In the current study, we evaluated the effect of abiotic factors (rainfall, relative humidity and temperature) in two eco-sites for two years on the incidence of AfRGM, and on the efficiency of the two parasotioids in the management of AfRGM. The incidence of AfRGM was significantly influenced by abiotic factors (rainfall, relative humidity and temperature). The percentage infestation increased with increase in rainfall and relative humidity. The trend was similar at both locations with the highest infestation recorded in October, and decreased in November. At both locations, percentage tiller infestation was greater in the rainy season of 2006 with more frequent rains than in 2007, with highest infestation recorded at Edozhigi in both years. Percentage parasitisms by the two parasitoids were found to have significant correlation with the abiotic factors. Heavy rains and high humidity significantly reduced the efficiency of the two parasitoids. On the contrast, the population and efficiency of the parasitoids were observed to increase with reducing rainfall, RH, but increasing temperature thus increasing the efficiency of the parasitoids later in the season with up to 70% parasitism when combined, with P. diplosisae dominating the field. The results suggest that abiotic factors played significant role on the incidence of AfRGM and the efficiency of these parasitoids and should be considered in the adoption of these parasitoids as bio-control agents of AfRGM.